Influence of thermal and acidic treatments on the morphology of a natural kaolinitic clay mineral - Pierre Ngue Song; Julien G. Mahy; Cédric Calberg; Antoine Farcy; Joachim Caucheteux; Nathalie Fagel; Stéphanie D. Lambert (Results in Surfaces and Interfaces, 2023)
In this work, a natural kaolinitic clay mineral from Kribi in Cameroon is modified by thermal and acidic treatments. The influence of these treatments on the physicochemical properties of the clays is studied using X-ray diffraction, Fourier transform infrared spectroscopy, nitrogen adsorption–desorption measurements, scanning electron microscopy, inductively coupled plasma–atomic emission spectroscopy and thermal analysis. Three calcination temperatures are explored: 600, 700 and 800 °C. The XRD pattern of the untreated clay showed that the natural clay mineral was mostly composed of kaolinite. Calcination at high temperatures allowed the amorphization of the natural kaolinitic clay mineral to obtain metakaolinite. This heat treatment of the natural clay mineral produced disintegration by rupture of the strong hydrogen bonds between the layers of the clay mineral. Heat treatment did not increase the specific surface area of the clay, which stayed around 20-30 m2/g. The acid treatment produced a high material texture modification giving microporous materials with a large surface area up to 315 m2/g with the sample previously calcined at 800 °C. The microporosity and mesoporosity increase is greater when the clay is calcined at high temperature. The morphology of the samples observed by SEM are modified by the acidic treatment. The initial two-dimensional stacking of particles evolves towards a narrower three-dimensional porous structure. These treatments open the way to produce highly porous clay materials that could be used as adsorbent materials for pollutant removal from water.